Analysis of a Stochastic Competitive Model with Saturation Effect and Distributed Delay - Ning, Wenxu; Liu, Zhijun; Wang, Lianwen; Tan, Ronghua (Methodology and computing in applied probability, 2021)
This work is concerned with a novel stochastic competitive model with saturation effect and distributed delay, in which two coupling noise sources are incorporated and the interspecific competition delayed terms show saturation effect. A good understanding of exponential extinction, extinction, persistence in the mean and permanence in time average of two species are gained. Also, with the help of Lyapunov function and the global attraction of positive solution, we derive the existence and uniqueness of stationary distribution. Our main results reveal that the coupling noise sources can significantly change the survival results of two species and affect the existence of a unique stationary distribution.